A Systematic Review of The Trends Research Scientific Reasoning Ability in Students' Biology Learning (2015-2024) - Wahyuni Arafani; Nurul Hidayah; Aris Doyan; Syarful Annam (Indonesian Publication Center, 2024)
One aspect that is part of 21st century skills is scientific reasoning ability. Scientific reasoning ability is important to know because it represents a collection of skills and abilities needed to complete tasks in the process of science investigation. Therefore, scientific reasoning ability should be trained and incorporated into the science learning process. This study aims to identify and analyze the research trends of scientific reasoning ability in biology learning. This research method is descriptive and analytical. The data used in this study were obtained from Google Scholar indexed documents from 2015-2024 using Publish or Perish and Dimension.ai. The research procedure uses PRISMA guidelines. The data identified and analyzed were the type of publication, the source of publication, and the title of scientific reasoning ability research in biology learning that was widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis showed that the trend of scientific reasoning ability research in learning biology indexed by Google Scholar from 2015 to 2024 experienced a fluctuating increase (the condition of the rise and fall of a data). Research trends with an increasing number of publications from 2015 to 2018. However, in 2019 and 2022 the research trend of scientific reasoning ability in biology learning decreased from the previous year and the research trend increased again in 2023. There are many documents in the form of book chapters, articles, edited books, monographs, preprints and proceedings that discuss research on scientific reasoning skills in learning biology. Keyword analysis shows that the most frequently occurring terms in this study include Scientific Reasoning Ability 273 times. This trend reflects the growing attention to scientific reasoning ability in scientific reasoning ability in biology learning and suggests the need for further efforts to improve research and applications in this area.